Life cycle analysis and assessment in civil engineering : towards an integrated vision. - International Symposium on Life-Cycle Civil Engineering 2018 : Ghent, Belgium); Caspeele, Robby; Taerwe, Luc; Frangopol, Dan M. (London : CRC Press, 2019)
This volume contains the papers presented at IALCCE2018, the Sixth International Symposium on Life-Cycle Civil Engineering (IALCCE2018), held in Ghent, Belgium, October 28-31, 2018. It consists of a book of extended abstracts and a USB device with full papers including the Fazlur R. Khan lecture, 8 keynote lectures, and 390 technical papers from all over the world. Contributions relate to design, inspection, assessment, maintenance or optimization in the framework of life-cycle analysis of civil engineering structures and infrastructure systems. Life-cycle aspects that are developed and discussed range from structural safety and durability to sustainability, serviceability, robustness and resilience. Applications relate to buildings, bridges and viaducts, highways and runways, tunnels and underground structures, off-shore and marine structures, dams and hydraulic structures, prefabricated design, infrastructure systems, etc. During the IALCCE2018 conference a particular focus is put on the cross-fertilization between different sub-areas of expertise and the development of an overall vision for life-cycle analysis in civil engineering. The aim of the editors is to provide a valuable source of cutting edge information for anyone interested in life-cycle analysis and assessment in civil engineering, including researchers, practising engineers, consultants, contractors, decision makers and representatives from local authorities.
Towards the use of UHPFRC in railway bridges: The rehabilitation of Buna BridgeOnline tracking of inputs, states and parameters of structural dynamic systems; State estimation of geometrically non-linear systems using reduced-order models; Modal strain-based damage identification on a prestressed concrete beam; Damage detection of steel bridge by numerical simulations and measurements; Parametric identification and damage assessment of real buildings; Deep neural network for structural damage detection in bridges; Vibration-based damage indicators for corrosion detection in tubular structures.
OCLC-licensed vendor bibliographic record.
Keywords: Engineering economy; Product life cycle; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior